2016
DOI: 10.1016/j.jsxm.2016.11.310
|View full text |Cite
|
Sign up to set email alerts
|

Considering Attachment and Partner Perceptions in the Prediction of Physical and Emotional Sexual Satisfaction

Abstract: Introduction. Attachment theory provides a framework for understanding sexual satisfaction;

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Though no work to date has studied perceptions of a partner’s sexual growth beliefs or sexual rejection sensitivity, prior research suggests that perceptions of growth mindsets are important predictors of individual performance in relevant domains (Fuesting et al, 2019). Moreover, higher perceived partner sexual satisfaction has been linked to higher sexual satisfaction for the self (Øverup & Smith, 2017), suggesting that metaperceptions related to sex play an important role in sexual satisfaction among couples.…”
Section: Sexual Growth Mindsetsmentioning
confidence: 99%
“…Though no work to date has studied perceptions of a partner’s sexual growth beliefs or sexual rejection sensitivity, prior research suggests that perceptions of growth mindsets are important predictors of individual performance in relevant domains (Fuesting et al, 2019). Moreover, higher perceived partner sexual satisfaction has been linked to higher sexual satisfaction for the self (Øverup & Smith, 2017), suggesting that metaperceptions related to sex play an important role in sexual satisfaction among couples.…”
Section: Sexual Growth Mindsetsmentioning
confidence: 99%
“…Cette différence entre les genres a aussi été observée dans une récente méta-analyse effectuée par Del Giudice (2011). De manière générale, les associations obtenues sur le plan de l'évitement de l'intimité sont similaires à celles recensées auprès de populations adultes en ce qui a trait à la satisfaction sexuelle (Stefanou et McCabe, 2012;Øverup et Smith, 2017) et à la communication des besoins sexuels (Khoury et Findlay, 2014 ;Davis et al, 2006). Les résultats semblent donc converger avec la théorie de l'attachement amoureux selon laquelle les adolescents qui rapportent un attachement évitant seraient particulièrement réticents à développer un lien intime avec leur partenaire (Tracy et al, 2003).…”
Section: Analysesunclassified
“…Selon Khoury et Findlay (2014), ces individus seraient d'ailleurs peut-être plus susceptibles de répondre activement à une baisse de la satisfaction sexuelle dans le couple (c.-à-d. en communiquant davantage leurs besoins sexuels) afin de maintenir sa cohésion. D'autre part, Øverup et Smith (2017) notent que, chez les couples adultes, l'anxiété d'abandon est associée à la satisfaction sexuelle seulement lorsque la satisfaction sexuelle perçue du partenaire est prise en compte. Ainsi, si son partenaire semble satisfait sexuellement, l'individu qui présente davantage d'anxiété d'abandon aurait alors tendance à être aussi satisfait, et vice et versa.…”
Section: Service Social -unclassified
“…For example, compared to securely attached couples, insecurely attached couples tend to have discrepant views about the desired level of intimacy (Millwood & Waltz, 2008). Moreover, insecure partners report less trust in their partners' availability and responsiveness (Mikulincer, 1998) and more sexual dissatisfaction (Gewirtz-Meydan & Finzi-Dottan, 2018;Øverup & Smith, 2017). In terms of the latter, attachment avoidance has been associated with less personal and physical satisfaction from sexual activity (Gewirtz-Meydan & Finzi-Dottan, 2018;Øverup & Smith, 2017), and attachment anxiety has been associated with concerns about the partner's sexual satisfaction (Øverup & Smith, 2017).…”
mentioning
confidence: 99%
“…Moreover, insecure partners report less trust in their partners' availability and responsiveness (Mikulincer, 1998) and more sexual dissatisfaction (Gewirtz-Meydan & Finzi-Dottan, 2018;Øverup & Smith, 2017). In terms of the latter, attachment avoidance has been associated with less personal and physical satisfaction from sexual activity (Gewirtz-Meydan & Finzi-Dottan, 2018;Øverup & Smith, 2017), and attachment anxiety has been associated with concerns about the partner's sexual satisfaction (Øverup & Smith, 2017). Gewirtz-Meydan and Finzi-Dottan (2018) found that needing reassurance was associated with high attachment anxiety in both men and women; notably, men's attachment anxiety was also associated with their female partners' need for reassurance.…”
mentioning
confidence: 99%